Nature of "memory" in T-cell mediated antibacterial immunity: cellular parameters that distinguish between the active immune response and a state of "memory". - North, R J (1975)
Immunizing infection in mice with Listeria monocytogenes resulted in the generation of two distinct states of immunological reactivity. There was generated (i) a short-lived state of active immunity that functioned to urgently eliminate the infection organism from the tissues and (ii) a long-lives state of increased immunological potential that enabled the host to respond to seconday infection in an accelerated manner. Short-lived active immunity was mediated by replicating T cells and expressed by activated macrophages, and it ended when these cell types disappeared from the tissue soon after complete elimination of the parasite. Long-lived immunological protential was associated with a persistent level of delayed sensitivity and with the presence of a small number of nonreplicating protective T cells. It is suggested that the state of delayed sensitivity represents a state of immunological T-cell memory of the cell-mediated type.